An approach for pillow plate heat exchangers design for single-phase applications. (25th January 2019) - Arsenyeva, Olga; Tran, Julian; Piper, Mark; Kenig, Eugeny
Highlights: A new design approach for pillow-plate heat exchangers (PPHEs) is presented. Optimal design of PPHEs for water heating and crude oil preheat train is found. PPHEs are compared with chevron-type plate heat exchangers. PPHEs are beneficial for significantly different cold and hot fluid flow rates. Abstract: Pillow-plate heat exchangers (PPHEs) represent a novel equipment type. For their application in industry, reliable preliminary design techniques are required. In this article, the existing methods for heat exchangers design are analysed and the approach for selecting the PPHE design with minimal heat transfer area is proposed. It is based on the mathematical model of thermal and hydraulic PPHE behaviour, in which the overall heat transfer coefficient and pressure drop in PPHEs are expressed through the fluid velocity. The estimation of fluid velocities in PPHE channels is based on the condition that the predefined allowable pressure drop is fully exploited. Two case studies for water heating and crude oil preheat train operating conditions are discussed, in which the flowrates of the fluids on the hot and cold sides differ significantly. The PPHE design with minimal heat transfer area for the considered case studies is presented, with specified pillow-plate geometry parameters and distance between pillow-plate panels. The resulting pressure drops and velocities in PPHEs channels as well as the obtained heat transfer surface areas are compared with existing data for chevron-type plate heat exchangers (PHEs) designed for the same operating conditions. This comparison shows that PPHEs have higher velocities in channels, longer plates and lower heat transfer area. It can be concluded that PPHEs can be successfully used for operating conditions, under which the flow rates for hot and cold fluid are significantly different and the application of chevron-type PHEs with single-pass arrangement is complicated.